Inspiring women of today : a strategic public communications campaign to raise the awareness for the Singapore Business & Professional Women's Association (SBPWA) (Appendix I to P). - Ho, Ruth See Wee. (2008)
(This FYP consists of 3 sections) Pulse Communications is a team of four final year female students from the School of Communication and Information, Nanyang Technological University, with a special interest in women’s issues. Pulse embarked on a strategic public communications campaign “Inspiring Women of Today” to assist Singapore Business & Professional Women’s Association (SBPWA) in raising its profile and awareness in Singapore.